PHASE DEFINE: POP-UP BOOK AS A MEDIA LEARNING ELEMENTARY SCHOOL STUDENT BASED INDIGENOUS SCIENCE 1,2,3,4 1 LOCAL WISDOM FARMERS VILLAGE SALT JONO - Tin Rosidah; Fitri Anisa; Nurihika Fitri Savira; Fitria Fatichatul Hidayah (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2018)
n pop-up book as a medium the introduction of local knowledge related knowledge native process of making salt jono to village of primary school age children primary school in order that he might the natural resources in the region. It also can foster the sense of love of country and proud of the local culture owned jono village. This study aims to know needs analysis students and teachers on the development of a pop-up book as a medium learning primary school student based indigenous science local wisdom farmers salt jono village, and developed. The development of this pop-up book research methods have research and development with the procedures used the development of which is a modification of 4d model that was triggered by thiagarajan (1974). The stage that have been conducted by namely define and design. During the preparatory phase of define the results showedthat knowledge of the production process salt in the village jono not yet used as the theme of primary school in their experiences in the. The procurement of media that are contextual and fun is really needed by the educator in the process of learning to support students understanding of the subject matter. A literature review and field work was carried out by means of interview, observation, and documentation. Based in pop-up book indigenous science local wisdom farmers salt jono village is hoped can be alternative media learning that can be used educator in creating an atmosphere of learning which interactive and fun and easy to understand students .Keywords: pop-up book, local wisdom, farmers salt Jono village, the learning.